Penggunaan Media Pembelajaran Policermat (Monopoli Cerdas Cermat) untuk Meningkatkan Hasil Belajar IPAS di Sekolah Dasar - Nur Pratiwi, Riska; Tryanasari, Dewi; Aidah Riyani, Denny Nur (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
This study aims to improve IPAS learning outcomes using Smart Monopoly media in class IV students at SDN Ngariboyo 4, Ngariboyo District, Magetan Regency. This type of research is Classroom Action Research. The instruments used were observation sheets and evaluation questions. The data analysis technique is quantitative. The media used is Smart Monopoly. The results showed that students' science learning outcomes had increased. In the pre-cycle, the average student learning outcome is 70, including the moderate category, and the proportion of student learning completeness is 30.76%. In cycle I, the average student learning outcomes and the proportion of student mastery increased to 74.23 and 38.46%. Cycle I did not meet the requirements of the experiment, and improvements were made. In cycle II, the average student learning outcomes were 90.76, included in the very good category, and the proportion of student learning completeness was 92.30% and met the research success criteria.